2020
DOI: 10.1186/s12886-020-01537-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of refractive outcomes after photorefractive keratectomy with different optical zones using Mel 90 excimer laser

Abstract: Background: A larger optical zone for photorefractive keratectomy may improve optical quality and stability. However, there is need for limiting ablation diameter in that a larger ablation diameter requires greater ablation depth, and minimizing ablation depth may reduce adverse effects on postoperative wound healing, haze and keratoectasia. In this study, we compared the changes in clinical outcomes and the degree of regression between a 6.0 mm optical zone and 6.5 mm optical zone following PRK. Methods: The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
2
0
2
Order By: Relevance
“…In our study, rf and rs were also decreased significantly. We observed that Kmax increased significantly in post-operative follow-ups, like Shin et al (24) After myopic ablation, the topography device recognizes the corneal ablation transition zone as the steepest part of the cornea and measures the Kmax value accordingly. This situation caused Kmax values to be found to be higher postoperatively.…”
Section: Discussionsupporting
confidence: 71%
“…In our study, rf and rs were also decreased significantly. We observed that Kmax increased significantly in post-operative follow-ups, like Shin et al (24) After myopic ablation, the topography device recognizes the corneal ablation transition zone as the steepest part of the cornea and measures the Kmax value accordingly. This situation caused Kmax values to be found to be higher postoperatively.…”
Section: Discussionsupporting
confidence: 71%
“…Also, as previously described in the literature, most treatment planning systems of excimer lasers use optical zones ranging between 6 and 6.5 mm with a general trend toward larger optical zones. Tose are comparable to the optical zones used in this study [32][33][34][35]. Terefore, the principle of the CPT ratio may be applied to excimer lasers from other manufacturers than the one used in this study.…”
Section: Discussionmentioning
confidence: 90%
“…We found no significant differences in the frequency of PRK-treated eyes with optic zones of 6 or 6.5 mm between those with and without myopic regression. Shin et al found no significant differences in regression between the 6.0-mm optical zone and the 6.5-mm optical zone over one year post-PRK [ 26 ]. This is inconsistent with the findings of Mohammadi et al, who reported a significant association between an intended optical zone < 6 mm and regression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%